Linear-g-hyperbranched and cyclodextrin-based amphiphilic block copolymer as a multifunctional nanocarrier - Zhao, Yamei; Tian, Wei; Yang, Guang; Fan, Xiaodong (Beilstein Journal of Organic Chemistry, 2014)
In this paper, a novel, multifunctional polymer nanocarrier was designed to provide adequate volume for high drug loading, to afford a multiregion encapsulation ability, and to achieve controlled drug release. An amphiphilic, triblock polymer (ABC) with hyperbranched polycarbonsilane (HBPCSi) and β-cyclodextrin (β-CD) moieties were first synthesized by the combination of a two-step reversible addition-fragmentation transfer polymerization into a pseudo-one-step hydrosilylation and quaternization reaction. The ABC then self-assembled into stable micelles with a core–shell structure in aqueous solution. These resulting micelles are multifunctional nanocarriers which possess higher drug loading capability due to the introduction of HBPCSi segments and β-CD moieties, and exhibit controlled drug release based on the diffusion release mechanism. The novel multifunctional nanocarrier may be applicable to produce highly efficient and specialized delivery systems for drugs, genes, and diagnostic agents.
Keywords: amphiphilic block copolymer; cyclodextrin polymer; hyperbranched polymer; multifunctionality; polymer nanocarrier

(untitled) - Allen, T. M.; Cullis, P. R. (Science, 2004)

(untitled) - Portney, N. G.; Ozkan, M. (Anal. Bioanal. Chem., 2006)

(untitled) - Saad, M.; Garbuzenko, O. B.; Ber, E.; Chandna, P.; Khandare, J. J.; Pozharov, V. P.; Minko, T. (J. Controlled Release, 2008)

(untitled) - Sawant, R. R.; Torchilin, V. P. (Soft Matter, 2010)

(untitled) - Minko, T.; Khandare, J. J.; Vetcher, A. A.; Soldatenkov, V. A.; Garbuzenko, O. B.; Saad, M.; Pozharov, V. P. (Fundam. Biomed. Technol., 2008)

(untitled) - Torchilin, V. P. (Adv. Drug Delivery Rev., 2006)

(untitled) - Thierry, B.; Al-Ejeh, F.; Khatri, A.; Yuan, Z.; Russell, P. J.; Ping, S.; Brown, M. P.; Majewski, P. (Chem. Commun., 2009)

(untitled) - McNeeley, K. M.; Karathanasis, E.; Annapragada, A. V.; Bellamkonda, R. V. (Biomaterials, 2009)

(untitled) - Karathanasis, E.; Chan, L.; Balusu, S. R.; D'Orsi, C. J.; Annapragada, A. V.; Sechopoulos, I.; Bellamkonda, R. V. (Biomaterials, 2008)

(untitled) - Zhang, R.; Wu, C.; Tong, L.; Tang, B.; Xu, Q.-H. (Langmuir, 2009)

(untitled) - Shi, D. (Adv. Funct. Mater., 2009)

(untitled) - Guo, R.; Zhang, L.; Qian, H.; Li, R.; Jiang, X.; Liu, B. (Langmuir, 2010)

(untitled) - Zhang, J.; Sun, H.; Ma, P. X. (ACS Nano, 2010)

(untitled) - Lahann, J. (Macromol. Rapid Commun., 2010)

(untitled) - Rösler, A.; Vandermeulen, G. W. M.; Klok, H.-A. (Adv. Drug Delivery Rev., 2001)

(untitled) - Torchilin, V. P. (Adv. Drug Delivery Rev., 2002)

(untitled) - Godwin, A.; Bolina, K.; Clochard, M.; Dinand, E.; Rankin, S.; Simic, S.; Brocchini, S. (J. Pharm. Pharmacol., 2001)

(untitled) - Pierri, E.; Avgoustakis, K. (J. Biomed. Mater. Res., Part A, 2005)

(untitled) - Zhang, Y.; Li, X.; Zhou, Y.; Wang, X.; Fan, Y.; Huang, Y.; Liu, Y. (Nanoscale Res. Lett., 2010)

(untitled) - Chandra, S.; Mehta, S.; Nigam, S.; Bahadur, D. (New J. Chem., 2010)

(untitled) - Lai, J. T.; Filla, D.; Shea, R. (Macromolecules, 2002)

(untitled) - Tian, W.; Fan, X.-D.; Liu, Y.-Y.; Jiang, M.; Huang, Y.; Kong, J. (J. Polym. Sci., Part A: Polym. Chem., 2008)

(untitled) - Note, C.; Koetz, J.; Kosmella, S.; Tiersch, B. (Colloid Polym. Sci., 2005)

(untitled) - Eguchi, M.; Du, Y.-Z.; Ogawa, Y.; Okada, T.; Yumoto, N.; Kodaka, M. (Int. J. Pharm., 2006)

(untitled) - Hong, H.; Mai, Y.; Zhou, Y.; Yan, D.; Cui, J. (Macromol. Rapid Commun., 2007)

(untitled) - Hu, Y.; Jiang, X.; Ding, Y.; Zhang, L.; Yang, C.; Zhang, J.; Chen, J.; Yang, Y. (Biomaterials, 2003)

(untitled) - Lee, S. C.; Kim, C.; Kwon, I. C.; Chung, H.; Jeong, S. Y. (J. Controlled Release, 2003)

(untitled) - Gaucher, G.; Dufresne, M. H.; Sant, V. P.; Kang, N.; Maysinger, D.; Leroux, J. C. (J. Controlled Release, 2005)

(untitled) - Zhang, X.; Cheng, J.; Wang, Q.; Zhong, Z.; Zhuo, R. (Macromolecules, 2010)

(untitled) - Lodge, T. P.; Rasdal, A.; Li, Z.; Hillmyer, M. A. (J. Am. Chem. Soc., 2005)

(untitled) - Shen, Y.; Jin, E.; Zhang, B.; Murphy, C. J.; Sui, M.; Zhao, J.; Wang, J.; Tang, J.; Fan, M.; Van Kirk, E.; Murdoch, W. J. (J. Am. Chem. Soc., 2010)

(untitled) - Miyata, K.; Kakizawa, Y.; Nishiyama, N.; Yamasaki, Y.; Watanabe, T.; Kohara, M.; Kataoka, K. (J. Controlled Release, 2005)

(untitled) - Liu, Y.-Y.; Fan, X.-D. (Biomaterials, 2005)

(untitled) - Aryal, S.; Prabaharan, M.; Pilla, S.; Gong, S. (Int. J. Biol. Macromol., 2009)

(untitled) - Siepmann, J.; Peppas, N. A. (Adv. Drug Delivery Rev., 2001)

(untitled) - Zuleger, S.; Lippold, B. C. (Int. J. Pharm., 2001)